NLBSIT: A New Lightweight Block Cipher Design for Securing Data in IoT Devices - H. A. Al-Ahdal, Abdulrazzaq; A. AL-Rummana, Galal; Shinde, G.N; K. Deshmukh, Nilesh (International Journal of Computer Sciences and Engineering, 2020)
Modern applications consist of different types of control devices and sensors that connect to the Internet. These applications are new approved technologies called the Internet of Things. Nowadays, these new technologies have gained a great interest in the field of research because of their existence in several diverse fields and due to the rapid development of these technologies. Communication between these devices generates a large amount of private and sensitive information and data between them. Therefore, maintaining the confidentiality of that data and information in the Internet of Things is of great importance. Mathematical cost (complex mathematical operations) and the number of cycles in traditional cryptographic algorithms leads to a large use of memory and energy waste for devices with limited resources, which makes traditional cipher algorithms inappropriate for Internet of Things devices. A fast and LW algorithm called NLBSIT has been proposed in this regard, which provides the requisite protection and resource constrained confidentiality of data on IoT devices. This algorithm (NLBSIT) uses a 64-bit key to encode 64-bit data, uses simple mathematical operations (XOR, XNOR, shifting, swapping), and uses the features of both the Feistel and SP Network architecture to achieve diffusion and confusion (increasing data security). The FELICS and MATLAB tools are used to simulate the NLBSIT algorithm. To execute this algorithm, various data types are used, such as text and images. The results of the simulation indicate the supremacy of the proposed algorithm in various areas, such as security, efficiency, less cycles (encryption and decryption), and less memory usage.